Assessment of the relationship between disease progression and goals of care by individuals with Duchenne muscular dystrophy and their caregivers. Issue 6 (16th February 2022) - Grossoehme, Daniel H.; Thienprayoon, Rachel; Sawnani, Hemant; Jenkins, Rachel; Rossman, Ian; Mosher, Kathryn; Friebert, Sarah
Abstract: Introduction/Aims: Most patients with Duchenne muscular dystrophy (DMD) in the US are diagnosed at about age 5 years. Some adolescents and young adults (AYAs) with DMD are now living into their fourth decade, yet AYAs and caregivers are frequently unprepared to address changes in goals of care due to disease progression. The hypothesis‐generating research question was how AYAs with DMD and their caregivers understand the relationship between physical changes and the need to change goals of care. Methods: Grounded theory design using data from N = 30 semi‐structured interviews ( n = 13 AYA; n = 17 caregivers) from two sites. Results: AYAs with DMD frequently defer considering and/or reconsidering goals of care based on (1) delays in diagnosis; (2) gradual, rather than episodic, disease progression; and (3) orientation to living in the present. Desire for autonomy motivates advance care planning and end‐of‐life treatment preferences for some. Discussion: Routine inquiry into AYA and caregiver goals for living may normalize goals of care conversations, maximizing patients' ability to process information, reflect on preferences, and articulate wishes. Discussing present‐day goals and abilities may invite conversation about future preferences. Framing conversations in terms of AYA autonomy may increase motivation to engage in such discussions. Abstract : See Editorial on pages 627–629 in this issue